Storage of ‘umbu-cajá’ pulp powder produced by lyophilization - Dyego da C. Santos; Ana P. T. Rocha; Josivanda P. Gomes; Emanuel N. A. de Oliveira; Esther M. B. de Albuquerque; Gilmar T. de Araujo (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT This work aimed to study the chemical and physical stability of ‘umbu-cajá’ powders produced by lyophilization during storage. ‘Umbu-cajá’ pulps formulated with different concentrations of gum arabic (10, 20 and 30%), previously frozen, were dehydrated in benchtop lyophilizer at -40 °C for 48 h and disintegrated to obtain the powder, which was stored in laminated packages for 180 days at ambient conditions, with physical, chemical and physico-chemical analyzes performed at the beginning and every 30 days of storage. According to the results, all investigated parameters were significantly altered throughout the storage, yet with less intense variations for important variables, such as ascorbic acid, reducing sugars and titratable acidity. At the end of storage, all powders were microbiologically safe.